Viral and bacterial infection among hospitalized-suspected influenza A/H5N1 patients in Indonesia, 2008-2009 (Faculty of Medicine Universitas Indonesia, 2012)
Background: Since a lot of suspected H5N1 cases with severe ARI manifestation were hospitalized and negative for H5N1, it raised a concern to investigate the other etiologies among hospitalized-suspected H5N1 cases. The aim of present study is to investigate the other respiratory pathogens of hospitalized-suspected H5N1 cases in which will provide valuable insight in the etiologies and epidemiology data of ARI. Methods: We tested the archived respiratory clinical specimens (nasal or throat swab, tracheal aspirate and bronchoalveolar lavage) that were already confirmed as negative H5N1 for 16 viruses and 8 bacteria existence by Multiplex PCR and Real-Time PCR from 230 hospitalized-suspected H5N1 cases received in July 2008 to June 2009. Results: Of the 230 hospitalized-suspected H5N1 cases, Klebsiella pneumoniae was the most dominant bacterial pathogen in children and adult. Moreover, the common viral pathogens in children was influenza A (non H5), while it was varied in adults as influenza A (non H5), Enterovirus, HRV A/B, Coronavirus 229E/NL63 were found very low. Bacterial mix infection of Klebsiella pneumoniae, Streptococcus pneumoniae and Haemophillus influenzae mainly occurred in children while co-infections of Klebsiella pneumoniae and Streptococcus pneumoniae were frequently found in adults. In addition, the major bacterial-viral mix infection found among children was influenza A and Klebsiella pneumoniae. Conclusion: From all of the samples tested, bacterial infections remain the most common etiologies of ARI in adults and children although there were infections caused by viruses. Mix infection of bacterial and viral also found among adults and children. (Med J Indones. 2012;21:77-82) Keywords: